2020
DOI: 10.1177/1440783319896413
|View full text |Cite
|
Sign up to set email alerts
|

‘Being together really helped’: Australian transgender and non-binary people and their animal companions living through violence and marginalisation

Abstract: This article explores the intersections of human and animal lives in the context of violence and marginalisation. It draws on two studies, the first involving a sub-sample of 23 open-ended survey responses completed by transgender and non-binary (TNB) people taken from a larger study exploring the intersections of animal- and human-directed violence, and the second involving eight interviews with TNB people focused on the meaning of animal companionship. Together, the findings suggest that animal companionship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…It is well documented that youth and adults turn to pets for physiological and emotional comfort during times of stress (Tomlinson et al, 2020). Furthermore, recent studies demonstrate that both pet ownership and positive engagement with pets help to mitigate associations between familial victimization and psychological stress in sexual and gender minority and majority samples (Riggs et al, 2018; Rosenberg et al, 2020). Although research on the effects of HAI among emerging adults is limited, these studies, when examined collectively, suggest that HAI may be a particularly beneficial and prevalent means of coping with the potential to foster both personal hardiness and resilience to psychological stress in SGM populations (Fuller & Riggs, 2019).…”
Section: Relationships and Bonds With Companion Animalsmentioning
confidence: 99%
“…It is well documented that youth and adults turn to pets for physiological and emotional comfort during times of stress (Tomlinson et al, 2020). Furthermore, recent studies demonstrate that both pet ownership and positive engagement with pets help to mitigate associations between familial victimization and psychological stress in sexual and gender minority and majority samples (Riggs et al, 2018; Rosenberg et al, 2020). Although research on the effects of HAI among emerging adults is limited, these studies, when examined collectively, suggest that HAI may be a particularly beneficial and prevalent means of coping with the potential to foster both personal hardiness and resilience to psychological stress in SGM populations (Fuller & Riggs, 2019).…”
Section: Relationships and Bonds With Companion Animalsmentioning
confidence: 99%
“…However, less is known about the role of companion animals in the lives of younger LGBTQ+ populations and the potential protective impact of relationships with companion animals on experiences of LGBTQ-related stressors. Recent studies conducted with LGBTQ+ adults experiencing family violence found that pet ownership and positive interactions with pets buffered the relationship between victimization by family members and psychological stress [49,50]. Additionally, a recent study found an indirect effect of exposure to interpersonal microaggressions on personal hardiness via human-animal interaction; increases in interpersonal microaggressions were related to increases in human-animal interaction, which in turn were related to increases in self-reported personal hardiness [51].…”
Section: Relationships With Companion Animals As a Protective Factormentioning
confidence: 99%
“…Indeed, many individuals perceive that companion animals are more reliable sources of socioemotional support than humans; this is particularly true among marginalized populations impacted by adverse social relationships and environments [ 119 , 120 , 121 , 122 ]. To this end, there is some evidence that pet ownership and other aspects of HAI (attachment to pets, positive engagement with pets, emotional comfort derived from pets) may help to mitigate the deleterious impacts of adverse experiences and stress on psychological wellbeing (i.e., anxiety and mood disorder symptoms; [ 29 , 120 , 123 , 124 , 125 ]). For example, prior studies provide evidence that: HAI may function as a protective factor that buffers the relation between intimate partner violence exposure and internalizing symptoms in children [ 123 ]; emerging adults seek out HAI as a coping strategy following exposure to sexual and gender minority stressors and, in turn, HAI fosters personal hardiness following adversity [ 126 ]; HAI buffers the impact of victimization on self-esteem among LGBTQ+ emerging adults [ 29 ]; and adults who experience familial abuse and live with an animal report less psychological distress than adults experiencing abuse who do not live with pets [ 124 ].…”
Section: Social Relationships the Stress Response And Perinatal Mental Healthmentioning
confidence: 99%